Optimization of 1H-indazol-3-amine derivatives as potent fibroblast growth factor receptor inhibitors. Issue 16 (15th August 2017) - Cui, Jing; Peng, Xia; Gao, Dingding; Dai, Yang; Ai, Jing; Li, Yingxia
Graphical abstract: In a continuing effort to develop more potent cellular activity of hit compound7r which was previously discovered by our group, several compounds harnessing fluorine substituents were designed, synthesized and biological evaluated. Additionally, the region extended out to the ATP binding pocket toward solvent was also explored. Abstract: Fibroblast growth factor receptor (FGFR) is a potential target for cancer therapy because of its critical role in promoting cancer formation and progression. In a continuing effort to improve the cellular activity of hit compound7r bearing an indazole scaffold, which was previously discovered by our group, several compounds harnessing fluorine substituents were designed, synthesized and biological evaluated. Besides, the region extended out to the ATP binding pocket toward solvent was also explored. Among them, compound2a containing 2, 6-difluoro-3-methoxyphenyl residue exhibited the most potent activities (FGFR1: less than 4.1 nM, FGFR2: 2.0 ± 0.8 nM). More importantly, compound2a showed an improved antiproliferative effect against KG1 cell lines and SNU16 cell lines with IC50 values of 25.3 ± 4.6 nM and 77.4 ± 6.2 nM respectively.